Learning resources and students’ academic performance in geography in Makueni county, Kenya - Munguti, Stephen (My University, 2016)
This study investigated the relationship between learning resources and students‟ academic performance in geography in KCSE in public secondary schools in Makueni County. The objectives of the study sought: to establish the variety of learning resources used in the teaching and learning of geography in public schools in Makueni County and their effect on KCSE performance in the subject in the county; to find out the availability of learning resources for the teaching and learning of geography in public schools in Makueni County and its effect on KCSE performance in the subject in the county; to establish the use of learning resources in the teaching and learning of geography in public schools in Makueni County and its effect on KCSE performance in the subject in the county; and to find out the relationship between teacher training on learning resources and its effect on KCSE performance in geography in public schools in Makueni County. The study was guided by the Classroom Instruction Theory using the descriptive survey design. Both stratified and simple random sampling methods were applied in drawing a sample. Data was collected from 422 respondents who included 29 principals, 30 teachers of geography and 363 Form Three students. Data was collected using questionnaires and an observation checklist. Questionnaires were used to collect data from principals, teachers and students. The observation checklist was used in observing geography lessons. Both descriptive and inferential statistics were used to analyse quantitative data and included means frequencies, crosstabulations, percentages, correlation and regression analysis. Qualitative data analysis was done using a mixed method of case by case analysis as well as cross case analysis. The findings of the study were: correlation between availability of learning resources and performance in geography at 0.401; correlation between the use of learning resources and geography performance at 0.631; correlation between variety of learning resources and performance in geography at 0.196 and finally, correlation between training of teachers and KCSE performance in geography at 0.197. Null hypotheses on variety, availability and use of resources were rejected while null hypothesis on training of teachers was adopted. The study therefore concluded that while access to variety of learning resources, availability of learning resources and use of resources in the teaching and learning process promoted academic performance in geography in KCSE in public secondary schools in Makueni County, pre-service teacher training on learning resources did not. Recommendations made were: to sensitize teachers to be innovative; teachers to use a variety of learning resources in teaching; school heads to encourage their teachers to attend in-service training; MOE and TSC to ensure further training opportunities to teachers; the content of training opportunities like symposia and workshops to be scrutinized and areas of weakness identified and strengthened; and finally, the use of emerging technology, especially ICT given more consideration in teaching/learning geography. Recommendations for further research were: duplicating the research to probably cover all of Kenya; establishing the content of the symposia and workshops, their usefulness to teachers, what can be done to improve their usefulness; and finally, conducting a multivariate study relating performance in geography with entry behaviour of learners into secondary school and use of learning resources in teaching/ learning be conducted